Negative electrode composite material and preparation and application thereof

By designing the fibrous fibrous structure and SNS2/FES2 three -phase interface in the negative electrode material of sodium ion batteries, the problem of low FES2 material conductivity and slow dynamic dynamic dynamic dynamics are solved, and the high -storage sodium capacity and electrochemical chemistry capacity and electrochemical chemistry are realized Improvement.

CN119381433AActive Publication Date: 2025-01-28JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411525592.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode material FeS2 has problems such as low conductivity, slow reaction kinetics and capacity attenuation, which is difficult to meet the needs of high energy density.

Method used

Design a sodium ion battery negative composite material, which uses a hard carbon -covered fibrous structure. The transition metal sulfide contains SNS2 and FES2, forming a three -phase interface, increasing the transmission dynamics of ions and electronics, and improving through nitrogen doping. Conductivity.

Benefits of technology

A higher sodium storage capacity is achieved, the capacity attenuation and structure degenerate are suppressed, and the stability of the electrochemical reaction dynamics and materials is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381433A_ABST
    Figure CN119381433A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a sodium ion battery negative electrode composite material as well as preparation and application thereof. The sodium ion battery negative electrode composite material comprises a carbon fiber inner layer and a hard carbon outer layer, the surface of the carbon fiber inner layer is loaded with transition metal sulfide, the transition metal sulfide comprises SnS2 and FeS2, and the FeS2 comprises a pyrite structure and a white iron ore structure; and the hard carbon outer layer is coated outside the carbon fiber inner layer and the transition metal sulfide. According to the invention, the SnS2 / FeS2 material is designed into a hard carbon coated fibrous structure, so that an electrolyte can be in full contact with the material, sufficient reaction active sites are provided, an ion transmission path can be shortened, and electrochemical reaction kinetics can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a negative electrode composite material and a preparation and application thereof. Background Art

[0002] Due to the limited resources, uneven distribution and high cost of lithium, it is not suitable for use in the field of large-scale energy storage. Sodium and lithium belong to the same main group elements, not only have similar physical and chemical properties and energy storage mechanisms, but also have the advantages of high earth abundance, low extraction technology difficulty and low cost. Therefore, sodium-ion batteries have very broad application prospects in the field of large-scale energy storage.

[0003] Among the negative electrode materials currently available for sodium-ion batteries, carbon-based materials have attracted much attention due to their advantages such as wide resources, stable structure and low preparation cost. Graphite negative electrode materials, which have been very successful in lithium-ion batteries, are difficult to embed sodium ions into them, thus limiting the application of graphite in sodium-ion batteries. Hard carbon is regarded as a negative electrode material for sodium-ion batteries with great development potential due to its large carbon layer spacing and special microstructure. Resin-based is an excellent precursor for preparing hard carbon, and the ideal molecular structure can be designed as needed. However, the increasing energy density requirements for sodium-ion batteries have prompted the development of negative electrode materials with higher sodium storage capacity. In the development of negative electrode materials for sodium-ion batteries, transition metal sulfide (TMS) compounds can be used relative to Na + / Na can react reversibly with sodium at a suitable low voltage and has a large theoretical capacity. FeS2 has low cost, common element composition, and a theoretical specific capacity of up to 894 mAh g -1 FeS2 has attracted much attention due to its characteristics such as low electrical conductivity, slow reaction kinetics, and large volume changes during the reaction, which lead to capacity decay and structural degradation. At present, the rational structural engineering of bifunctional carbon-based composites has become an effective way to improve the electrochemical performance of FeS2 anodes. The construction of heterostructures composed of binary or multi-component metal sulfides has also improved the sodium storage performance. The heterojunction interface with the addition of multiple components increases the active reaction sites and improves the ion storage performance. However, the heterojunction interface will gradually passivate during repeated and asynchronous conversion / alloying-dealloying processes. At the same time, soluble intermediate reaction products are still weakening the reaction kinetics. In summary, it is necessary to develop a new material that can overcome the problems of capacity decay and structural degradation and inhibit the passivation process while providing higher sodium storage capacity. Summary of the invention

[0004] The present invention aims to solve the above problems and provides a sodium ion battery negative electrode composite material. By designing the SnS2 / FeS2 material into a hard carbon-coated fibrous structure, not only can the electrolyte be fully in contact with the material and have sufficient reaction active sites, but also the ion transmission path can be shortened and the electrochemical reaction kinetics can be improved.

[0005] According to the technical solution of the present invention, the negative electrode composite material includes a carbon fiber inner layer and a hard carbon outer layer; the surface of the carbon fiber inner layer is loaded with transition metal sulfides, the transition metal sulfides include SnS2 and FeS2, and the FeS2 includes a pyrite structure and a marcasite structure; the hard carbon outer layer is coated on the outside of the carbon fiber inner layer and the transition metal sulfides.

[0006] Specifically, the transition metal sulfide is a discontinuous coating layer, and the hard carbon outer layer covers the transition metal sulfide and contacts the carbon fiber inner layer.

[0007] The sodium ion battery negative electrode composite material of the present invention presents a fibrous structure as a whole, which helps to shorten the electron / ion transmission path. Among transition metal sulfides, SnS2 / FeS2 materials have a high sodium storage specific capacity. The heterostructure interface of FeS2 materials is regulated by SnS2 to obtain a three-phase interface, and the obtained three-phase interface helps to stabilize the interface. Specifically, FeS2 has two structures, pyrite and marcasite, of which the cubic pyrite is superior to the orthorhombic marcasite in sodium storage performance. However, the passivation phenomenon of the two-phase heterojunction interface will be aggravated during the charge and discharge process. In order to further improve the electrochemical properties of FeS2 materials, the heterostructure interface of FeS2 materials is regulated by SnS2 to obtain a three-phase interface, thereby further improving the transmission of ions and electrons and helping to stabilize the interface.

[0008] Furthermore, the diameter of the carbon fiber inner layer is 1-10 μm.

[0009] Furthermore, the carbon fiber inner layer and the hard carbon outer layer are doped with nitrogen. Specifically, the total amount of nitrogen doping accounts for 2-5wt% of the negative electrode composite material.

[0010] Furthermore, the hard carbon outer layer has a thickness of 5-10 nm and can be formed by calcining resin.

[0011] Furthermore, the transition metal sulfide satisfies at least one of the following conditions:

[0012] The transition metal sulfide accounts for 30-50% of the total mass of the negative electrode composite material (in the negative electrode composite material of the sodium ion battery, the loading mass ratio of SnS2 / FeS2 is 30-50%);

[0013] In the transition metal sulfide, the atomic ratio of iron to tin in the SnS2 and the FeS2 is (3-5):1;

[0014] The particle size of the transition metal sulfide is 10-100 nm.

[0015] The second aspect of the present invention provides a method for preparing a sodium ion battery negative electrode composite material, comprising the following steps:

[0016] S1: soaking the biomass material in a mixed solution of an iron source and a tin source, and freeze-drying the biomass material to obtain a mixed material;

[0017] S2: calcining the mixed material and the sulfur-containing resin under an inert gas atmosphere to obtain the sodium ion battery negative electrode composite material.

[0018] Furthermore, the biomass material contains a fibrous structure, which is selected from one or more of cellulose, bamboo fiber, coconut shell, rice straw, cotton stalk skin, and sugarcane bagasse.

[0019] Furthermore, in the step S1, before the biomass material is immersed in the mixed solution of the iron source and the tin source, a step of removing impurities is also included.

[0020] Furthermore, the specific operation of removing impurities includes: firstly alkali washing the biomass material for 1.5-3 hours, washing with water until the pH value is 7-8; then acid washing for 1.5-3 hours, washing with water until the pH value is 6-7; and finally drying.

[0021] Furthermore, the alkaline solution used in the alkaline washing is selected from one or both of potassium hydroxide solution and sodium hydroxide solution, and its concentration can be 0.5-1 mol / L;

[0022] The acid solution used for pickling is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid, and its concentration can be 0.5-1 mol / L, preferably 0.5-1 mol / L hydrochloric acid;

[0023] The solid-to-liquid ratio (mass volume ratio of biomass material to acid solution or alkaline solution) of the alkaline washing and acid washing is 1:50-200 (g:mL);

[0024] The drying temperature is 70-90° C. and the drying time is 10-20 hours.

[0025] Furthermore, in step S1, the biomass material is immersed in the mixed solution of the iron source and the tin source for 10-16 hours.

[0026] Further, the iron source is selected from one or more of ferric chloride, ferrous chloride, ferric fluoride, ferric acetate, ferric sulfate and ferric nitrate;

[0027] The tin source is selected from one or more of tin chloride, stannous chloride, tin sulfate and tin acetate;

[0028] In the mixed solution of the iron source and the tin source, the concentrations of the iron source and the tin source are both 0.01-0.1M.

[0029] Furthermore, in the mixed solution of the iron source and the tin source, the molar ratio of iron to tin is 1-3:1.

[0030] Furthermore, in step S1, freeze drying is performed by freezing in liquid nitrogen for 1.5-4 hours, and after freezing, the mixture is placed in a vacuum freeze dryer for drying.

[0031] Furthermore, the inert gas is selected from one or more of nitrogen, argon, and helium, and the gas flow rate of the inert gas can be 40-80 mL / min.

[0032] Furthermore, in step S2, the mass ratio of the mixed material to the sulfur-containing resin is 1:5-10; the calcination temperature is 1000-1500°C, the heating rate can be 15-20°C / min, and the calcination time is 2-5h.

[0033] Furthermore, the sulfur-containing resin as a sulfur source and a carbon source can be gasified at a certain temperature (the severe thermal decomposition temperature of the sulfur-containing resin is 500-700° C.), and can be selected from one or more of thiourea resin, polysulfide epoxy resin, polyphenylene sulfide (PPS resin), and the like.

[0034] Preferably, in order to avoid the presence of impurities and obtain a product with higher purity, in the step S2, when the mixed material and the sulfur-containing resin are calcined, the mixed material and the sulfur-containing resin are placed in two adjacent containers (such as crucibles).

[0035] Furthermore, in the step S2, after calcining the mixed material and the sulfur-containing resin, the step of calcining in an NH3 atmosphere is further included to nitrogen-dope the carbon material.

[0036] Furthermore, the conditions for calcination under NH3 atmosphere are: NH3 gas flow rate is 40-80 mL / min, calcination temperature is 500-700°C, heating rate can be 2-5°C / min, and calcination time is 2-5h.

[0037] A third aspect of the present invention provides a sodium ion battery negative electrode plate, comprising the above-mentioned sodium ion battery negative electrode composite material or the sodium ion battery negative electrode composite material prepared by the above-mentioned preparation method.

[0038] A fourth aspect of the present invention provides a sodium ion battery, comprising the above-mentioned sodium ion battery negative electrode plate.

[0039] Compared with the prior art, the technical solution of the present invention has the following advantages: the overall design of the sodium ion battery negative electrode composite material of the present invention is a fibrous structure (formed by coating with carbon fiber as the inner layer), which is conducive to shortening the ion / electron transmission path; the theoretical specific capacity is as high as 894mAh g -1 FeS2 is used to coat carbon fiber, and SnS2 is used to regulate the heterojunction of FeS2 material to obtain a three-phase interface of SnS2 / pyrite FeS2 / marcasite FeS2, which improves the transmission of ions and electrons and helps to stabilize the interface; the outermost hard carbon coating can effectively inhibit and buffer the volume expansion and enhance the structural stability; the conductivity of the material can be further improved by doping with nitrogen; the preparation method is simple and easy to control, the structure and morphology of the synthesized product are stable, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the SEM image of the sodium ion battery negative electrode composite material (SnS2 / pyrite FeS2 / marcasite FeS2@NCF) in Example 1.

[0041] Figure 2 This is a transmission electron micrograph of the hard carbon outer layer in the sodium ion battery negative electrode composite material (SnS2 / pyrite FeS2 / marcasite FeS2@NCF) in Example 1.

[0042] Figure 3 This is a transmission electron microscopy image of the three-phase interface in the sodium ion battery negative electrode composite material (SnS2 / pyrite FeS2 / marcasite FeS2@NCF) in Example 1 (P: pyrite; M: marcasite). DETAILED DESCRIPTION

[0043] Biomass-based and resin-based materials are excellent precursors for preparing hard carbon, which can be used to obtain hard carbon materials suitable for sodium storage. However, since hard carbon materials are not enough to meet the growing energy density requirements of sodium-ion batteries, the development of higher-capacity negative electrode materials is prompted. In the development of negative electrode materials for sodium-ion batteries, transition metal sulfide (TMS) compounds can be used in the production of negative electrode materials relative to Na + / Na can react reversibly with sodium at a suitable low voltage and has a large theoretical capacity. FeS2 has low cost, common element composition, and a theoretical specific capacity of up to 894 mAh g -1 However, FeS2 has problems such as low conductivity, slow reaction kinetics, and large volume changes during the reaction, which lead to capacity decay and structural degradation. In addition, FeS2 has two structures, pyrite and marcasite. Among them, cubic pyrite is better than orthorhombic marcasite in sodium storage performance. However, the passivation phenomenon of the dual-phase heterojunction interface will be aggravated during the charge and discharge process.

[0044] Based on this, the present invention provides a sodium ion battery negative electrode composite material, comprising a carbon fiber inner layer and a hard carbon outer layer; a transition metal sulfide is loaded on the surface of the carbon fiber inner layer. The transition metal sulfide is a discontinuous coating layer, recorded as the middle layer, and its material composition includes SnS2 and FeS2, and FeS2 includes two structures of pyrite and marcasite; the hard carbon outer layer is coated on the outside of the carbon fiber inner layer and the middle layer.

[0045] Specifically, the transition metal sulfide of the transition metal sulfide layer is a three-phase interface composed of SnS2, pyrite FeS2 and marcasite FeS2. The hard carbon outer layer covers the middle layer and contacts the carbon fiber inner layer.

[0046] In some preferred embodiments, transition metal sulfides account for 30-50% of the total mass of the negative electrode composite material of the sodium ion battery, for example, it can be 30%, 35%, 40%, 45%, 50%, etc.; wherein the iron-tin atomic ratio is 3-5:1, for example, it can be 3:1, 3.5:1, 4:1, 5:1, etc.; the particle size of the transition metal sulfide is 10-100nm, for example, it can be 10nm, 30nm, 50nm, 70nm, 100nm, etc.

[0047] In some preferred embodiments, the carbon fiber inner layer and the hard carbon outer layer are doped with nitrogen, and the doped nitrogen element can further synergistically improve the conductivity of the composite material. The total amount of nitrogen doping accounts for 2-5wt% of the negative electrode composite material, for example, it can be 2wt%, 3wt%, 4wt%, 5wt%, etc.

[0048] The method for preparing the above-mentioned sodium ion battery negative electrode composite material may include the following steps:

[0049] S1: soaking the biomass material (the material is selected from one or more of cellulose, bamboo fiber, coconut shell, rice straw, cotton stalk skin, bagasse) in a mixed solution of an iron source (selected from one or more of ferric chloride, ferrous chloride, ferric fluoride, ferric acetate, ferric sulfate and ferric nitrate) and a tin source (selected from one or more of tin chloride, stannous chloride, tin sulfate and tin acetate) for 10-16 hours, immersing in liquid nitrogen and freezing for 1.5-4 hours, and after freezing, placing in a vacuum freeze dryer for drying to obtain a mixed material;

[0050] S2: In an inert gas atmosphere (selected from one or more of nitrogen, argon, and helium, with a gas flow rate of 40-80 mL / min), a mixed material with a mass ratio of 1:5-10 (for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.) and a sulfur-containing resin (selected from one or more of thiourea resin, polysulfide epoxy resin, PPS resin, etc.) are calcined at a calcination temperature of 1000-1500°C, a heating rate of 15-20°C / min, and a calcination time of 2-5h to obtain the sodium ion battery negative electrode composite material.

[0051] In some preferred embodiments, the biomass material further includes a step of removing impurities before being immersed in the mixed solution of the iron source and the tin source. The specific operation includes: firstly using an alkaline solution (selected from one or both of a potassium hydroxide solution and a sodium hydroxide solution) with a concentration of 0.5-1 mol / L (for example, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc.) to alkali-wash the biomass material for 1.5-3 h (for example, 1.5 h, 2 h, 2.5 h, 3 h, etc.), and rinsing with water until the pH value is 7-8 (for example, 7.2, 7.5, 7.7, 8, etc.); then using a concentration of 0.5 -1mol / L (for example, it can be 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, etc.) acid solution (selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, etc.) pickling for 1.5-3h (for example, it can be 1.5h, 2h, 2.5h, 3h, etc.), rinsed with water until the pH value is 6-7 (for example, it can be 6, 6.2, 6.5, 6.7, 7, etc.); finally, dried at 70-90℃ (for example, it can be 70℃, 75℃, 80℃, 85℃, 90℃, etc.) for 10-20h (for example, it can be 10h, 12h, 15h, 18h, 20h, etc.). The solid-liquid ratio of alkali washing and acid washing is 1:50-200 (g:mL), for example, 1:50 (g:mL), 1:100 (g:mL), 1:150 (g:mL), 1:200 (g:mL), etc.

[0052] In some preferred embodiments, in the mixed solution of iron source and tin source, the concentration of iron source and tin source are both 0.01-0.1M, for example, 0.01M, 0.03M, 0.05M, 0.07M, 0.09M, 0.1M, etc.; the molar ratio of iron to tin is 1-3:1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc.

[0053] In some preferred embodiments, in order to avoid the appearance of impurities and obtain a product of higher purity, in step S2, when the mixed material and the sulfur-containing resin are calcined, the mixed material and the sulfur-containing resin are placed in two adjacent containers (such as crucibles). Specifically, the container containing the sulfur-containing resin can be placed at the front end of the calcination container (such as a tubular furnace). During the calcination process, the sulfur-containing resin is gasified and reacts with the mixed material in the rear container to obtain a sandwich structure material with an inner layer of carbon fiber, a middle layer of SnS2 / FeS2 material, and an outermost layer of resin-derived hard carbon (carbon has low solubility in FeS2, and carbon will be deposited on the surface when S and Fe react), which is recorded as SnS2 / FeS2@CF sodium ion battery negative electrode composite material.

[0054] In some preferred embodiments, in step S2, after calcining the mixed material and the sulfur-containing resin, the step further includes calcining in an NH3 atmosphere to nitrogen-dope the carbon material.

[0055] Specifically, the conditions for calcination under NH3 atmosphere are: NH3 gas flow rate is 40-80mL / min, for example, it can be 40mL / min, 50mL / min, 60mL / min, 70mL / min, 80mL / min, etc.; the calcination temperature is 500-700℃, for example, it can be 500℃, 550℃, 600℃, 650℃, 700℃, etc.; the heating rate is 2-5℃ / min, for example, it can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, etc.; the calcination time is 2-5h, for example, it can be 2h, 3h, 4h, 5h, etc.; and a sodium ion battery negative electrode composite material recorded as SnS2 / FeS2@NCF is obtained.

[0056] The obtained sodium ion battery negative electrode composite material (SnS2 / FeS2@CF or SnS2 / FeS2@NCF) can be used to prepare sodium ion battery negative electrode sheets and further used to prepare sodium ion batteries.

[0057] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0058] Example 1

[0059] (1) 10 g of cellulose was placed in 500 mL of 1 M potassium hydroxide solution and stirred for 2 h. The material was then repeatedly rinsed with deionized water to adjust the pH value of the solution to 7. The material was then placed in 500 mL of 1 M hydrochloric acid solution and stirred for 2 h. The solution was then repeatedly rinsed with water to adjust the pH value of the solution to 7 and dried in an oven at 80 °C for 12 h.

[0060] (2) 1.2 g of ferric nitrate and 1.2 g of tin chloride were added to 500 mL of deionized water, and the mixed solution was stirred for 1 h. 5 g of cellulose from which impurities had been removed was soaked in the stirred mixed solution for 12 h. The mixture was then immersed in liquid nitrogen and frozen for 2 h. After freezing, it was placed in a vacuum freeze dryer for drying. The material obtained after drying was recorded as material No. 1.

[0061] (3) Take 3g of material No. 1, and then put material No. 1 and thiourea resin into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing thiourea resin placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 15℃ / min, the calcination time is 2h, and the calcination temperature is 1000℃. After the calcination, a sandwich structure material with an inner layer of carbon fiber, a middle layer of SnS2 / FeS2 material, and an outermost layer of resin-derived hard carbon is obtained, which is recorded as SnS2 / FeS2@CF.

[0062] (4) The SnS2 / FeS2@CF material is placed in a crucible and calcined in a tube furnace under NH3 atmosphere, and the gas flow rate can be 80 mL / min. The heating rate can be 2°C / min, the calcination time is 2 h, and the calcination temperature is 500°C to obtain a sodium ion battery negative electrode composite material recorded as SnS2 / FeS2@NCF.

[0063] Example 2

[0064] (1) Take 10g of cellulose and place it in 500mL of 1M sodium hydroxide solution and stir it for 2h. Then rinse the material repeatedly with deionized water to make the pH value of the solution reach 7; then place the material in 500mL of 1M hydrochloric acid solution and stir it for 2h. Then rinse it repeatedly with water to make the pH value of the solution 7, and place it in an oven at 80 degrees to dry for 12h.

[0065] (2) 400 mg of ferric chloride and 600 mg of tin chloride were added to 250 mL of deionized water, and the mixed solution was stirred for 1 h. 5 g of cellulose from which impurities had been removed was soaked in the stirred mixed solution for 12 h. The mixture was then immersed in liquid nitrogen and frozen for 2 h. After freezing, it was placed in a vacuum freeze dryer for drying. The material obtained after drying was recorded as material No. 1.

[0066] (3) Take 3g of material No. 1, and then put material No. 1 and thiourea resin into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing thiourea resin placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 15℃ / min, the calcination time is 2h, and the calcination temperature is 1000℃. After the calcination, a sandwich structure material with an inner layer of carbon fiber, a middle layer of SnS2 / FeS2 material, and an outermost layer of resin-derived hard carbon is obtained, which is recorded as SnS2 / FeS2@CF.

[0067] (4) The SnS2 / FeS2@CF material is placed in a crucible and calcined in a tube furnace under an NH3 atmosphere, and the gas flow rate can be 80 mL / min. The heating rate can be 5°C / min, the calcination time is 2 h, and the calcination temperature is 500°C, to obtain a sodium ion battery negative electrode composite material recorded as SnS2 / FeS2@NCF.

[0068] Example 3

[0069] (1) Take 10g of coconut shell and put it into 500mL of 1M potassium hydroxide solution and stir it for 2h. Then rinse the material repeatedly with deionized water to make the pH value of the solution reach 7; then put the material into 500mL of 1M hydrochloric acid solution and stir it for 2h. Then rinse it repeatedly with water to make the pH value of the solution 7, and put it into an oven at 80 degrees to dry for 12h.

[0070] (2) Take 2 g of ferric sulfate and 1.2 g of tin chloride and add them to 500 mL of deionized water. The mixed solution is stirred for 1 hour. 5 g of cellulose from which impurities have been removed is soaked in the stirred mixed solution for 12 hours. The mixture is then immersed in liquid nitrogen and frozen for 2 hours. After freezing, it is placed in a vacuum freeze dryer for drying. The material obtained after drying is recorded as material No. 1.

[0071] (3) Take 3g of material No. 1, and then put material No. 1 and thiourea resin into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing thiourea resin placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 15℃ / min, the calcination time is 2h, and the calcination temperature is 1000℃. After the calcination, a sandwich structure material with an inner layer of carbon fiber, a middle layer of SnS2 / FeS2 material, and an outermost layer of resin-derived hard carbon is obtained, which is recorded as SnS2 / FeS2@CF.

[0072] (4) The SnS2 / FeS2@CF material is placed in a crucible and calcined in a tube furnace under NH3 atmosphere, and the gas flow rate can be 80 mL / min. The heating rate can be 2°C / min, the calcination time is 2 h, and the calcination temperature is 500°C to obtain a sodium ion battery negative electrode composite material recorded as SnS2 / FeS2@NCF.

[0073] Example 4

[0074] (1) Take 10g of bamboo fiber and put it into 500mL of 1M potassium hydroxide solution and stir it for 2h. Then rinse the material repeatedly with deionized water to make the pH value of the solution reach 7; then put the material into 500mL of 1M hydrochloric acid solution and stir it for 2h. Then rinse it repeatedly with water to make the pH value of the solution 7, and put it into an 80 degree oven to dry for 12h.

[0075] (2) Take 2 g of ferric sulfate and 1.2 g of tin chloride and add them to 500 mL of deionized water. The mixed solution is stirred for 1 hour. 5 g of cellulose from which impurities have been removed is soaked in the stirred mixed solution for 12 hours. The mixture is then immersed in liquid nitrogen and frozen for 2 hours. After freezing, it is placed in a vacuum freeze dryer for drying. The material obtained after drying is recorded as material No. 1.

[0076] (3) Take 3g of material No. 1, and then put material No. 1 and thiourea resin into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing thiourea resin placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 15℃ / min, the calcination time is 2h, and the calcination temperature is 1000℃. After the calcination, a sandwich structure material with an inner layer of carbon fiber, a middle layer of SnS2 / FeS2 material, and an outermost layer of resin-derived hard carbon is obtained, which is recorded as SnS2 / FeS2@CF.

[0077] (4) The SnS2 / FeS2@CF material is placed in a crucible and calcined in a tube furnace under NH3 atmosphere, and the gas flow rate can be 80 mL / min. The heating rate can be 2°C / min, the calcination time is 2 h, and the calcination temperature is 500°C to obtain a sodium ion battery negative electrode composite material recorded as SnS2 / FeS2@NCF.

[0078] Comparative Example 1

[0079] (1) Take 10g of cellulose and place it in 500mL of 1M potassium hydroxide solution and stir it for 2h. Then rinse the material repeatedly with deionized water to make the pH value of the solution reach 7; then place the material in 500mL of 1M hydrochloric acid solution and stir it for 2h. Then rinse it repeatedly with water to make the pH value of the solution 7, and place it in an oven at 80 degrees to dry for 12h.

[0080] (2) 1.2 g of tin chloride was added to 500 mL of deionized water and stirred for 1 h. 5 g of cellulose from which impurities had been removed was soaked in the solution for 12 h. The mixture was then immersed in liquid nitrogen and frozen for 2 h. After freezing, the mixture was placed in a vacuum freeze dryer for drying. The material obtained after drying was recorded as material No. 1.

[0081] (3) Take 3g of material No. 1, and then put material No. 1 and sulfur powder into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing sulfur powder placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 5℃ / min, the calcination time is 2h, and the calcination temperature is 700℃. After the calcination, a sodium ion anode composite material with an inner layer of carbon fiber and an outer layer of SnS2 is obtained, which is recorded as SnS2@CF.

[0082] Comparative Example 2

[0083] (1) Take 10g of cellulose and place it in 500mL of 1M potassium hydroxide solution and stir it for 2h. Then rinse the material repeatedly with deionized water to make the pH value of the solution reach 7; then place the material in 500mL of 1M hydrochloric acid solution and stir it for 2h. Then rinse it repeatedly with water to make the pH value of the solution 7, and place it in an oven at 80 degrees to dry for 12h.

[0084] (2) 1.2 g of ferric nitrate and 3.6 g of tin chloride were added to 500 mL of deionized water, and the mixed solution was stirred for 1 h. 5 g of cellulose from which impurities had been removed was soaked in the stirred mixed solution for 12 h. The mixture was then immersed in liquid nitrogen and frozen for 2 h. After freezing, it was placed in a vacuum freeze dryer for drying. The material obtained after drying was recorded as material No. 1.

[0085] (3) Take 3g of material No. 1, and then put material No. 1 and thiourea resin into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing thiourea resin placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 15℃ / min, the calcination time is 2h, and the calcination temperature is 1000℃. After the calcination, a sandwich structure material with an inner layer of carbon fiber, a middle layer of SnS2 / pyrite FeS2 material, and an outermost layer of resin-derived hard carbon is obtained, which is recorded as SnS2 / pyrite FeS2@CF sodium ion anode composite material.

[0086] (4) The SnS2 / pyrite FeS2@CF material is placed in a crucible and calcined in a tube furnace under NH3 atmosphere, and the gas flow rate can be 80 mL / min. The heating rate can be 2°C / min, the calcination time is 2 h, the calcination temperature is 500°C, and the material after calcination is recorded as SnS2 / pyrite FeS2@NCF sodium ion anode composite material.

[0087] Comparative Example 3

[0088] (1) Take 10g of cellulose and place it in 500mL of 1M potassium hydroxide solution and stir it for 2h. Then rinse the material repeatedly with deionized water to make the pH value of the solution reach 7; then place the material in 500mL of 1M hydrochloric acid solution and stir it for 2h. Then rinse it repeatedly with water to make the pH value of the solution 7, and place it in an oven at 80 degrees to dry for 12h.

[0089] (2) 1.2 g of ferric nitrate was added to 500 mL of deionized water and stirred. Then, 5 g of cellulose from which impurities had been removed was immersed in the stirred mixed solution for 12 h. The mixture was then immersed in liquid nitrogen and frozen for 2 h. After freezing, the mixture was placed in a vacuum freeze dryer for drying. The material obtained after drying was recorded as material No. 1.

[0090] (3) Take 3g of material No. 1, and then put material No. 1 and sulfur powder into two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing sulfur powder placed at the front, and then transfer the two crucibles to a tubular furnace. The atmosphere in the tubular furnace is nitrogen, and the gas flow rate can be 80mL / min. The heating rate can be 5℃ / min, the calcination time is 2h, and the calcination temperature is 700℃. After the calcination, the inner layer is carbon fiber and the outer layer is pyrite FeS2 / marcasite FeS2, which is recorded as pyrite FeS2 / marcasite FeS2@CF sodium ion anode composite material.

[0091] Results Analysis

[0092] The materials synthesized in Examples 1-4 and Comparative Examples 1-3 were used as negative electrode active materials, carbon black as a conductive agent, and CMC (carboxymethyl cellulose) as a binder. The negative electrode was prepared according to the ratio of negative electrode active material: conductive agent: binder = 8:1:1. The metal sodium sheet was used as the positive electrode, and 1.0 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether was used as the electrolyte. NCF2032 button batteries were assembled in an argon glove box. The GCD (constant current charge and discharge test) was tested in a voltage window of 0.01-2V using a Land battery test system.

[0093] (1) The specific test process of the first discharge capacity, first charge capacity and first coulomb efficiency is as follows:

[0094] At 25°C, the battery was discharged at a constant current density of 100 mA / g to 0.01 V to obtain the first discharge capacity; then, the battery was charged at a constant current density of 100 mA / g to 2 V to obtain the first charge capacity; the first coulomb efficiency = first charge capacity / first discharge capacity*100%. The test results of the first discharge capacity, first charge capacity and first coulomb efficiency are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] The results in Table 1 show that the button cells of the materials prepared in Examples 1-4 all have a high initial discharge capacity of more than 890 mAh / g, while the first discharge capacity of Comparative Example 1 is only 107.8 mAh / g. Due to the characteristics of suitable multiphase heterojunction structure, abundant active sites, fast ion transport channels and structural stability, the fiber-structured SnS2 / FeS2@NCF material has outstanding sodium storage capacity.

[0099] (2) The specific test process of capacity retention rate is as follows: at a temperature of 25°C, discharge at a current density of 500 mA / g to 0.01 V; then charge at a current density of 500 mA / g to 2 V, and record the charge gram capacity at this time as the charge gram capacity of the first cycle; cycle the above charge and discharge steps for 200 cycles, and record the charge gram capacity of the 200th cycle; capacity retention rate = charge gram capacity of the 200th cycle / charge gram capacity of the first cycle*100%. The test results of capacity retention rate are shown in Table 2.

[0100] Table 2

[0101] Current density 500mA / g Capacity retention rate (%) Example 1 91.8 Example 2 91.2 Example 3 90.3 Example 4 92.2 Comparative Example 1 82.5 Comparative Example 2 85.2 Comparative Example 3 83.6

[0102] The results in Table 2 show that the button batteries made of the materials prepared in Examples 1-4 all have a relatively high cycle retention rate (up to 92.2%) and excellent cycle stability, while the capacity retention rates of Comparative Examples 1-3 are all lower than those of the Examples.

[0103] In summary, the SnS2 / FeS2@NCF material with a reasonable fiber structure has good conductivity, and good mechanical properties can alleviate the volume change during the cycle. Through reasonable process adjustment, it not only exerts the characteristics of stable material structure, but also has the characteristics of high specific capacity, thus improving the overall electrochemical performance of the electrode.

[0104] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A negative electrode composite material, characterized in that: It includes a carbon fiber inner layer and a hard carbon outer layer; the surface of the carbon fiber inner layer is loaded with transition metal sulfides, the transition metal sulfides include SnS2 and FeS2, and the FeS2 includes a pyrite structure and a marcasite structure; the hard carbon outer layer is coated on the outside of the carbon fiber inner layer and the transition metal sulfides.

2. The negative electrode composite material according to claim 1, characterized in that: At least one of the following conditions is met: The diameter of the carbon fiber inner layer is 1-10 μm; The carbon fiber inner layer and the hard carbon outer layer are doped with nitrogen; The thickness of the hard carbon outer layer is 5-10 nm.

3. The negative electrode composite material according to claim 1, characterized in that: The transition metal sulfide satisfies at least one of the following conditions: The transition metal sulfide accounts for 30-50% of the total mass of the negative electrode composite material; In the transition metal sulfide, the atomic ratio of iron to tin in the SnS2 and the FeS2 is (3-5):1; The particle size of the transition metal sulfide is 10-100 nm.

4. A method for preparing a negative electrode composite material, characterized in that: The following steps are included: S1: soaking the biomass material in a mixed solution of an iron source and a tin source, and freeze-drying the biomass material to obtain a mixed material; S2: calcining the mixed material and the sulfur-containing resin under an inert gas atmosphere to obtain the negative electrode composite material.

5. The preparation method according to claim 4, characterized in that: In the step S1, The biomass material is selected from one or more of cellulose, bamboo fiber, coconut shell, rice straw, cotton stalk skin, and sugarcane bagasse; The method further comprises the step of removing impurities before the biomass material is immersed in the mixed solution of the iron source and the tin source; The iron source is selected from one or more of ferric chloride, ferrous chloride, ferric fluoride, ferric acetate, ferric sulfate and ferric nitrate; The tin source is selected from one or more of tin chloride, stannous chloride, tin sulfate and tin acetate; In the mixed solution of the iron source and the tin source, the molar ratio of iron to tin is (1-3):1; The mass molar ratio of the biomass material to the iron source in the mixed solution is (2000-500) g: 1 mol The freeze drying is performed by freezing in liquid nitrogen for 1.5-4 hours, and vacuum drying is performed after the freezing is completed.

6. The preparation method according to claim 4, characterized in that: In the step S2, The mass ratio of the mixed material to the sulfur-containing resin is 1:(5-10); During the calcination process, the mixed material does not directly contact the sulfur-containing resin; The calcination temperature is 1000-1500° C. and the calcination time is 2-5 hours.

7. The preparation method according to claim 4, characterized in that: In the step S2, after calcining the mixed material and the sulfur-containing resin, the step of calcining under an NH3 atmosphere is also included.

8. The preparation method according to claim 7, characterized in that: The conditions for calcination under NH3 atmosphere are: NH3 gas flow rate is 40-80 mL / min, calcination temperature is 500-700°C, and time is 2-5 h.

9. A negative electrode plate, characterized in that: The invention comprises the negative electrode composite material according to any one of claims 1 to 3 or the negative electrode composite material prepared by the preparation method according to any one of claims 4 to 8.

10. A sodium ion battery, characterized in that: Including the negative electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • A sodium ion battery electrode material and a preparation method thereof

    CN109192942A

  • MXene composite material, preparation method and application thereof, and preparation method of sodium ion battery negative electrode

    CN117219758A

  • Carbon fiber coated hard carbon material as well as preparation method and application thereof

    CN117923463A

  • Method for preparing FeS2 / C hollow microspheres based on spray drying and application of FeS2 / C hollow microspheres

    CN118016850A

  • Iron-based porous carbon sodium ion battery composite negative electrode material and preparation method thereof

    CN118213510A